Learning Interventions to Improve Academic Ability in Slow Learners: Literature Review - Sarah Kemala Oktaviani; M. Izha Afdwikki; Bunga Aisya; Pasha Dwi Novita; Iftita Rahmi (Psikologi Prima, 2026)
Slow learning is a condition in which students have a below-average learning rate, necessitating a specialized approach to the learning process. This study aims to review various learning interventions used to enhance the academic abilities of students with learning difficulties. The method used was a systematic literature review of 12 relevant articles to explore how various forms of learning interventions enhance the academic abilities of slow learners. The study results indicate that the most effective interventions include mentoring with a special guidance teacher, constructivist learning models, practice methods, repeated reading techniques and cloze procedures, and token economy strategies. These interventions can significantly enhance numeracy skills, early literacy, learning motivation, and social interaction in slow learners. However, several studies also highlight the lack of teacher training and the use of individualized education programs as ongoing challenges. The success of interventions depends heavily on the involvement of teachers, parents, and a supportive school environment. Therefore, integrated and adaptive learning strategies are essential to optimally support the development of slow learners' academic abilities.